Analisis EWOM, Citra Merek, Dukungan Selebriti, dan E-Referral dalam Pembelian Produk Fashion Muslim di E-Commerce - Subkhan, Farid; Firdaus, Astrid Callista (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2025)
Research Aim: To examine the impact of EWOM, brand image, celebrity endorsement, and e-referral on purchasing decisions for Muslim fashion products through E-Commerce. Method: A mixed-method approach with 150 quantitative respondents and 20 qualitative participants in Jakarta, Depok, Bekasi, Bogor, and Tangerang. SPSS was used for analysis. Findings: This study suggests celebrity endorsement significantly impacts customer purchases of Muslim fashion products through E-Commerce. Theoretical Contribution: This study provides a new theoretical contribution by demonstrating that digital marketing communication variables such as e-referral, brand image, and EWOM cannot work alone to influence purchase decisions but must be combined with celebrity endorsement. Practical Implications: E-Commerce businesses should maximize collaborations with celebrity endorsers to boost market penetration and consumer trust. Research limitation: Limited to specific regions and four marketing variables, suggesting future research on other factors influencing online purchasing decisions.